ESTIMASI NILAI VaR PORTOFOLIO MENGGUNAKAN FUNGSI ARCHIMEDEAN COPULA - SUHARTO, AULIA ATIKA PRAWIBTA; DHARMAWAN, KOMANG; SUMARJAYA, I WAYAN (E-Jurnal Matematika, 2017)
Value at Risk explains the magnitude of the worst losses occurred in financial products investments with a certain level of confidence and time interval. The purpose of this study is to estimate the VaR of portfolio using Archimedean Copula family. The methods for calculating the VaR are as follows: (1) calculating the stock return; (2) calculating descriptive statistics of return; (3) checking for the nature of autocorrelation and heteroscedasticity effects on stock return data; (4) checking for the presence of extreme value by using Pareto tail; (5) estimating the parameters of Achimedean Copula family; (6) conducting simulations of Archimedean Copula; (7) estimating the value of the stock portfolio VaR. This study uses the closing price of TLKM and GGRM. At 90% the VaR obtained using Clayton, Gumbel, Frank copulas are 0.9562%, 1.0189%, 0.9827% respectively. At 95% the VaR obtained using Clayton, Gumbel, Frank copulas are 1.2930%, 1.2522%, 1.3152% respectively. At 99% the VaR obtained using Clayton, Gumbel, Frank copulas are 2.0327%, 1.9164%, is 1.8678% respectively. In conclusion estimation of VaR using Clayton copula yields the highest VaR.
Keywords: Portfolio; Value at Risk; Copula; Arhimedean Copula